One iguana two iguanas : a story of accident, natural selection, and evolution - Collard, Sneed B. (Tilbury House Publishers, 2018)
Natural selection and speciation are all but ignored in children<U+2019>s nonfiction. To help address this glaring deficiency, award-winning children<U+2019>s science writer Sneed Collard traveled to the Galapagos Islands to see for himself, where Charles Darwin saw, how new species form. The result is this fascinating story of two species of iguana, one land-based and one marine, both of which developed from a single ancestor that reached the islands millions of years ago. The animals evolved in different directions while living within sight of one another. How is that possible? Collard uses the iguanas to explore Charles Darwin<U+2019>s great discovery.